2003
DOI: 10.1542/peds.111.5.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Supplementation on Linear Growth, Body Composition, and Growth Factors in Preterm Infants

Abstract: Zinc supplementation has a positive effect on linear growth in premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 24 publications
10
104
1
1
Order By: Relevance
“…The lack of effect on weight in their study may have been due to factors like low sample size (N=52), formula feed and the fact that their study cohort comprised of VLBW infants. Similar findings were also noted by Gomez et al 3 in his study of 36 preterm infants. The authors found significant effect of zinc supplementation on length but not on weight gain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of effect on weight in their study may have been due to factors like low sample size (N=52), formula feed and the fact that their study cohort comprised of VLBW infants. Similar findings were also noted by Gomez et al 3 in his study of 36 preterm infants. The authors found significant effect of zinc supplementation on length but not on weight gain.…”
Section: Discussionsupporting
confidence: 91%
“…Zinc deficiency in infants has been shown to have an adverse impact on growth and immunity in many studies 2 . Several studies have demonstrated the benefit of zinc supplementation in low birth infants with regard to growth and prevention of infections [2][3][4][5][6][7] However, some studies have shown marginal or no effect 8 , It is with this view that the present study is undertaking to evaluate the effectiveness of zinc supplementation in LBW infants in our set up.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 3 studies conducted in developed countries (Spain and Canada), 2 studies among preterm infants showed positive effect on plasma zinc concentrations and linear growth(3,4) and 1 on LBW infants showed no effect(5). However, no significant effect on weight gain was VOLUME 47 __ OCTOBER 17, 2010 SAZAWAL AND BLACK EFFECT OF ORAL ZINC SUPPLEMENTATION observed in any of these studies (3)(4)(5). The available evidence for the effect of zinc supplementation on growth among low birth weight infants from developing countries setting is from India (2 studies)(6,7), Bangladesh (1 study)(8), Chile (1 study) (9) and Brazil (1 study) (10).…”
Section: E D I T O R I a L E D I T O R I A L E D I T O R I A L E D I mentioning
confidence: 87%
“…Zinc plays important roles in various physiologic functions in growth, development, and sexual maturity in males [16,21]. Zinc also plays biological roles in antioxidant properties, lipid metabolism, insulin resistance, immune response, sperm physiology and hepatic injury [3,26,34,39].…”
Section: Introductionmentioning
confidence: 99%